ANALISIS RASIONALITAS INVESTOR TERHADAP PEMILIHAN SAHAM DAN PENENTUAN PORTOFOLIO OPTIMAL DENGAN MODEL INDEKS TUNGGAL DI BEJ (Dengan ILQ 45 Sebagai Faktor Perhitungan) - Edy Suryawardana (Universitas Semarang, 2020)
The investor decide their large alternatives investation influenced by several factors. Particulary the stock investation would influenced by stock market condition correlated with stock pricing. Based on 17 stock which analized with an index model, it gets 3 stock in the portofolio optimal compasition. that compasitions trap on the stock from another industries sector. the result of this research have some conclusion with deciding optimal portofolio based on the an index models.key word : retrun saham, Beta, Risk free, Excess return to beta, cut of rate, portofolio efisien, portofolio optimal, model indeks tunggal, indeks LQ-45